You can simplify this expression with PEMDAS (parentheses, exponents, multiplication/division, addition/subtraction)
Start with the expressions in the parentheses:
4-7=-3
4+7=11
The expression now reads -2(-3)+5(11). Now, simplify the multiplication expressions:
-2*-3=6
5*11=55
The expression is 6+55 which is 61.
Hope this helps!!
Answer:
They have the same mustard flavor!
Answer: the equation is
5x^2 -30x - 25
Step-by-step explanation:
A quadratic equation is one in which the highest power of the unknown is 2.
The general form of a quadratic equation is expressed as
ax^2 + bx + c
Where c is a constant and a is the leading coefficient
Assuming we want to write the quadratic equation in x, from the information given, the given roots are 5 and 1 and the leading coefficient is 5. We will just multiply the expression by the leading coefficient.
Therefore, the linear factors of the quadratic will be (x-5) and (x-1)
With the leading coefficient as 5, the equation becomes
5(x-5)(x-1)
= 5(x^2 - x - 5x + 5)
= 5(x^2 - 6x + 5)
= 5x^2 -30x - 25
Her tax is $3198.
3.9/100=0.039.
0.039*8200=$3198.
7 were in each pack because orginally he had 28 he gave four away. 7*4=28